2019
DOI: 10.1186/s13550-018-0468-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential usefulness of 68Ga-citrate PET/CT in detecting infected lower limb prostheses

Abstract: BackgroundProsthetic joint infections may lead to failures of total joint arthroplasty. Radionuclide imaging can play a diagnostic role in identifying such infections, which require two-stage exchange arthroplasty (instead of simple revision surgery performed in non-infected cases). Although 18F-FDG PET/CT has emerged as a novel diagnostic tool in this setting, the clinical usefulness of 68Ga-citrate PET/CT has not been previously investigated. This single-center prospective study was designed to address this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 24 publications
(28 reference statements)
1
36
0
Order By: Relevance
“…These findings are consistent with our finding that 68 Ga-citrate is less likely to accumulate in inflammatory lesions with no active infection compared to 18 F-FDG. Again, a more recent study found 68 Ga-citrate was more specific than 18 F-FDG in distinguishing infected lower limb prosthesis from sterile inflammation [26]. This critical role must be explored further due to the limited number of post-infective lesions we had in our study.…”
Section: ▶Fig 3 a 18 F-fdg And B 68mentioning
confidence: 82%
“…These findings are consistent with our finding that 68 Ga-citrate is less likely to accumulate in inflammatory lesions with no active infection compared to 18 F-FDG. Again, a more recent study found 68 Ga-citrate was more specific than 18 F-FDG in distinguishing infected lower limb prosthesis from sterile inflammation [26]. This critical role must be explored further due to the limited number of post-infective lesions we had in our study.…”
Section: ▶Fig 3 a 18 F-fdg And B 68mentioning
confidence: 82%
“…It has the advantages of high spatial resolution, good image quality, low radiation dose, and the potential for accurate anatomical localization [4,10,11]. Extensive literature has compared [ 18 F]FDG with [ 68 Ga]Ga-citrate for the diagnosis of bone infection-related diseases, and showed different results [13,16,17,27,28]. However, distinguishing bone infection from AL or physiological in ammation with [ 18 F]FDG remains challenging [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies by Salomäki et al [17]. and Tseng et al [16]. have demonstrated that [ 18 F]FDG is unable to distinguish between bone infection and physiological healing or non-infectious complications after bone surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations